Kualitas Pelayanan Administrasi Terpadu Kecamatan dalam Optimalisasi Pelayanan Publik: (Studi pada Kantor Kecamatan Kalidawir, Kabupaten Tulungagung) - Akhmad Rifai; Hayat Hayat; Hirshi Anadza (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The quality of public service is one of the indicators of the success of local governments in the context of regional autonomy. This research examines the implementation of the Integrated Administrative Services Program (PATEN) in Kalidawir District, Tulungagung Regency, as a strategy to bring administrative services closer to the community. This study aims to determine the quality of PATEN services and identify the inhibiting factors in optimizing the conduct of public services. The method used is descriptive qualitative method. Data were collected through observation, documentation, and interviews, and then analyzed interactively using the Miles and Huberman model. This study adopts five dimensions of service quality according to Zeithaml, Berry, and Parasuraman, namely: physical evidence, reliability, responsiveness, assurance, and empathy. The research findings indicate that the implementation of PATEN in Kalidawir District has good performance in terms of service infrastructure, procedural accuracy, responsiveness, and transparency. The inclusivity of services is supported by facilities such as child-friendly rooms and breastfeeding rooms. The staff always implements SOP, provides timely services, and maintains professional behavior. However, there are two main obstacles that hinder the optimization of services: inadequate infrastructure for the elderly and persons with disabilities, as well as limited public understanding of service procedures. These challenges affect access, efficiency, and perceptions of service delivery. This study concludes that although PATEN services in Kalidawir District meet general standards, improving inclusive facilities and communication strategies is essential for more equitable and effective service outcomes.